Удосконалення управління розвитком підприємств машинобудівної галузі - Фоменко, А. В.; Кучмай, Ю. І. (НТУ "ХПІ", 2014)
В статті розглянуто сутність управління розвитком підприємства та уточнено його економічний зміст. Описані основні проблеми управління машинобудівними підприємствами та розглянуто сучасний стан машинобудівної галузі країни. Зроблені висновки про необхідність удосконалення системи управління розвитком підприємств машинобудівної галузі.

The article considers the essence of management of development company and clarifying its economic content. Describes the basic problem management machine-building enterprises and the present state of the machine-building industry in the country. Conclusions about the need to improve management systems development of enterprises machine-building industry. Established that in order to improve the current state of engineering companies need highly skilled management system to implement. And also continuously monitor the major components of the external and internal environment and constantly draw conclusions about the availability requirements change. Determined that to improve engineering companies and increase competitive products need to hold a set of measures for effective management of development.
Improving development management engineering industry
Keywords: машинобудування; промисловість; фінансово-економічна криза; стратегія розвитку; management development of enterprises; machine building; financial and economic crisis; development strategy; industry